Características poblacionales del cambute, Strombus galeatus (Gastropoda: Strombidae) en el Parque Marino Ballena, Pacífico, Costa Rica (1999-2003) - Arroyo Mora, Daisy (2008)
Marine parks and reserves are important for biodiversity conservation and as sustainable places for recovery of fishery resources, especially for those species of economic importance such as the Pacific conch Strombus galeatus. Independent surveys, from 1999 to 2003 were done in three areas in the park, by snorkeling and/or scuba diving. A total of 168 live snails were captured, and 120 of them were marked with plastic tags, albeit none were recaptured. Conchs were found on sandy and rocky bottoms, with young protected in corals or rocks. The population was mostly composed by young adults (50% of the popula- tion; mean length 162.2mm), with a 50:50 sex ratio. Density was 683 conchs/ha which reflects a relatively good population condition for the area. This park has natural barriers, allowing conchs to move along the area.